Abundance of C‐terminal binding protein isoform is a prerequisite for exit from pluripotency in mouse embryonic stem cells. Issue 12 (12th June 2018) - Suh, Min Young; Kim, Tae Wan; Lee, Han‐Teo; Shin, Jihoon; Kim, Jae‐Hwan; Jang, Hyonchol; Kim, Hye Ji; Kim, Seong‐Tae; Cho, Eun‐Jung; Youn, Hong‐Duk
ABSTRACT: Unlike lower organisms, mammals have 2 C‐terminal binding protein (Ctbp) isoforms, Ctbp1 and Ctbp2. Ctbp2 is revealed as a key factor involved in determining cell fate decisions by regulating the epigenetic state in active embryonic stem cell (ESC) genes. However, the molecular mechanism underlying how Ctbp1 and Ctbp2 have different roles remains elusive. Here we demonstrate that Ctbp isoform abundance is important for mouse embryonic ESCs (mESCs) to exit from pluripotency. Temporal expression patterns of Ctbp isoforms were quite different; Ctbp2 is more highly expressed in mESCs and decreases during differentiation, while Ctbp1 is constantly expressed at a lower level. Ctbp2 knockdown, but not Ctbpl knockdown, in mESCs resulted in impaired exit from pluripotency. Interestingly, Ctbp1 and Ctbp2 overexpression in Ctbp2 ‐knockdown mESCs leads to exiting from pluripotency in a manner similar to that of wild‐type mESCs. Quantification of Ctbp1 and Ctbp2 revealed that differentiation ability correlates with abundance of Ctbp isoform in undifferentiated mESCs, suggesting that a sufficient amount of Ctbp isoform is a prerequisite for exiting from pluripotency. The results support the contention that 2 redundant Ctbp isoforms regulate elaborate differentiation via temporally distinctive regulatory patterns in mESCs.—Suh, M. Y., Kim, T. W., Lee, H.‐T., Shin, J., Kim, J.‐H., Jang, H., Kim, H. J., Kim, S.‐T., Cho, E.‐J., Youn, H.‐D. Abundance of C‐terminal binding protein isoformis a prerequisite for exit from pluripotency in mouse embryonic stem cells. FASEB J . 32, 6423–6435 (2018). www.fasebj.org